2011
DOI: 10.1002/hon.1017
|View full text |Cite
|
Sign up to set email alerts
|

Cell of origin fails to predict survival in patients with diffuse large B‐cell lymphoma treated with autologous hematopoietic stem cell transplantation

Abstract: Diffuse large B-cell lymphoma (DLBCL) includes two prognostically-important subtypes, the germinal center B-cell (GCB) and the non-GCB types. The aim of this study was to evaluate immunohistochemical approaches for predicting the survival of patients with DLBCL following autologous hematopoietic stem cell transplantation (AHSCT). We identified 62 patients with DLBCL who either had an initial complete remission (17 patients) or received salvage chemotherapy for relapsed or refractory disease (45 patients), foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Intensified chemotherapy with rituximab possibly improves survival in younger patients with nongerminal DLBCL compared with standard R-CHOP [37]. In a retrospective study of patients with DLBCL treated with ACST as first-line therapy, Gu et al suggested that the cell of origin fails to predict survival [38]. The prognostic relevance of BCL2 is more complex.…”
Section: Discussionmentioning
confidence: 99%
“…Intensified chemotherapy with rituximab possibly improves survival in younger patients with nongerminal DLBCL compared with standard R-CHOP [37]. In a retrospective study of patients with DLBCL treated with ACST as first-line therapy, Gu et al suggested that the cell of origin fails to predict survival [38]. The prognostic relevance of BCL2 is more complex.…”
Section: Discussionmentioning
confidence: 99%
“…The other methods to determine COO, or MYC and BCL2 expressions such as IHC have their own limitations. For instance, in some studies, non-GCB phenotype do not correlate with bad prognosis (30)(31)(32) as confirmed by a recent meta-analysis (33) and concordance between IHC and GEP is imperfect (34). Even though concurrent overexpression of both MYC and BCL2 had been associated with a poor outcome in several studies (18,35), the recent European Society for Medical Oncology consensus (36) does not yet recommended changing therapeutic strategy according to these results due to problems in reproducibility of manual or visual IHC scoring and lack of agreement on the optimal positivity thresholds throughout the laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] The results, however, have been controversial as the concordance with GEP results is imperfect to varying degrees and, in some studies, IHC results do not correlate with prognosis. [11][12][13] Furthermore, both the GCB and ABC subtypes of DLBCL as defined by GEP are heterogeneous and contain biological subgroups that have different prognoses and may require different therapeutic approaches. Therefore, a stratification of DLBCL patients into subgroups that are biologically homologous and prognostically meaningful, and that are more predictive than the overall categories of GCB and ABC is needed, thereby facilitating therapeutic decisions.…”
Section: Introductionmentioning
confidence: 99%